2018
DOI: 10.1007/s11302-018-9630-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of P2X7 receptor-dependent enhancement of neuromuscular transmission in pannexin 1 knockout mice

Abstract: P2X7 receptors are present in presynaptic membranes of motor synapses, but their regulatory role in modulation of neurotransmitter release remains poorly understood. P2X7 receptors may interact with pannexin 1 channels to form a purinergic signaling unit. The potential mechanism of P2X7 receptor-dependent modulation of acetylcholine (ACh) release was investigated by recording miniature endplate potentials (MEPPs) and evoked endplate potentials (EPPs) in neuromuscular junctions of wildtype (WT) and pannexin 1 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
5
16
0
Order By: Relevance
“…Next, we tested the contribution of P2X7 receptors, which might provide specific Ca 2+ influx to nerve terminals, to the regulation of ACh secretion in NMJs. Like we demonstrated recently [10], the activation of P2X7 receptors by their exogenous agonist BzATP (30 µM) at the NMJs of WT mice did not change either spontaneous or evoked ACh release during rhythmic synaptic activity ( Figure 3A,B).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Next, we tested the contribution of P2X7 receptors, which might provide specific Ca 2+ influx to nerve terminals, to the regulation of ACh secretion in NMJs. Like we demonstrated recently [10], the activation of P2X7 receptors by their exogenous agonist BzATP (30 µM) at the NMJs of WT mice did not change either spontaneous or evoked ACh release during rhythmic synaptic activity ( Figure 3A,B).…”
Section: Resultssupporting
confidence: 83%
“…Further analysis of the specific activity of P2X7 receptors was performed in the NMJs of Panx1 −/− mice. Recently, we found that in the motor synapses of Panx1 −/− mice but not in those of WT mice, BzATP induces the potentiation of evoked ACh release, which can be prevented by the inhibition of CaMKII or L-type VDCCs [10]. Here, we reproduced the potentiating effect of BzATP in the NMJs of Panx1 −/− mice (Figure 4 A-C).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations